Phytodiversity Conservation for Disaster Risk Reduction in Bhoj Ramsar Site, Madhya Pradesh - Garg, Arti (Indian Forester, 2023)
Bhoj Ramsar site in Madhya Pradesh is a rich repository of about 530 species of angiosperms which are differentiated into herbs, shrubs, trees, climbers, lianas and hydrophytes, both floating and submerged. Most species are economically and medicinally important and help in livestock sustenance with few plant species reported for the first time from Madhya Pradesh. The dense floristic elements and compact tree canopies support phytodiversity of the miniature ecosystem for uninterrupted food chain, shoreline stabilization and mitigation of climate change impacts. Judicious management activities of the lake and associated wetlands are therefore recommended with caution against damage to the extant floristic components which are of value in mitigating the adversities of climate change for community sustenance in general, and the Ramsar site in particular.